2018
DOI: 10.1155/2018/2709401
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Canal Course and the Position of the Mental Foramen by Panoramic X-Ray in Chilean Individuals

Abstract: The object of this study was to analyse the morphology and morphometry of the mandibular canal (MC) course and the mental foramen (MF) position in relation to the inferior teeth by panoramic X-ray (PAN). Vertical linear measurements were taken of each hemimandible to obtain the length of the distances analysed. We studied the MF position in relation to inferior premolar roots and the relation between the MC and mandibular teeth roots (MCR). The MF was usually located between the apices of the first and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
6
0
2
Order By: Relevance
“…The mandible forms the lower part of the face and is composed of the body and two rami ( 1 ). The posterior region of the mandible is highly vascularized due to the presence of the inferior alveolar bundles and the submandibular fossa, making it vulnerable during implant installation, third molar surgery, mandible osteotomy, or endodontic treatments ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mandible forms the lower part of the face and is composed of the body and two rami ( 1 ). The posterior region of the mandible is highly vascularized due to the presence of the inferior alveolar bundles and the submandibular fossa, making it vulnerable during implant installation, third molar surgery, mandible osteotomy, or endodontic treatments ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The course of the inferior alveolar nerve (IAN) and its relation to the teeth has been studied by several investigators [10][11][12]. The variation in the location of MF and pattern of inferior alveolar nerve canal (IANC) has been studied by various investigators in different populations [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…From there, it runs obliquely downward and forward in the ramus and then travels horizontally forward and ends at the mental foramen. 3 Previous sexual dimorphism studies on dry mandibles, cadavers, and radiographic images have indicated that the course of the inferior alveolar canal varies with sex. [4][5][6] Radiographic imaging is remarkably useful as an aid for sex determination, as it can provide a variety of morphological information noninvasively.…”
Section: Introductionmentioning
confidence: 99%